A method for preparing a composite material bipolar plate for an all-vanadium liquid flow battery
By mixing graphite with organic polymer polymers, and combining the dual screw extrusion mechanism to prepare the mother -granularity powder, the bipolar board of the composite material is prepared to solve the problems that the bipolar board conductivity and mechanical properties are difficult to take into account in existing technologies. , Realize the preparation of high -conductivity, mechanical properties and gas tightness.
Patent Information
- Application Number
- CN202411283853.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-13
AI Technical Summary
In the prior art, when preparing composite bipolar plates, it is difficult to achieve high conductivity, mechanical properties and airtightness at the same time, and the melt blending technology is prone to destroy the graphite structure, resulting in a decrease in conductivity and a decrease in bending strength.
Use graphite and organic polymer polymer to mix after the ball grinding, obtain the main mix of organic polymer polymers to cover graphite, and prepare female powder powder through the double screw extrusion mechanism to prepare bipolar plates in combination with mold pressure technology to control the main mix The proportion of maternal powder is optimized to optimize the decentralization effect of carbon materials, polymers and graphite.
It improves the curvature performance, gas tightness and conductivity of the bipolar board, reduce the thickness of the graphite surface polymer layer, reduce the contact resistance, and shorten the mixing time, and improve production efficiency.
Smart Images

Figure CN118800924B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of composite material bipolar plates, and in particular to a preparation method of a composite material bipolar plate for an all-vanadium liquid flow battery. Background Art
[0002] As one of the key materials in the flow battery stack, the bipolar plate supports the electrode and ion membrane, conducts and collects the current generated during the charge and discharge process, and blocks the electrolyte on both sides. Therefore, the ideal bipolar plate needs to have good conductivity, electrochemical stability, corrosion resistance, and a certain mechanical strength.
[0003] The existing technology often uses carbon materials of different sizes and dimensions to reduce the amount of carbon materials used and improve the conductivity. The large-sized graphite plays the role of forming a conductive network skeleton. The large contact area between large-sized graphites helps to reduce the contact resistance between conductive carbon materials, thereby improving the conductivity of the bipolar plate. Small-sized carbon materials have a large specific surface area and can be used as secondary fillers to fill the pores between graphite particles and connect the conductive path, thereby improving the conductivity of the composite bipolar plate.
[0004] In order to solve the mixing problem between carbon materials and polymers, and between carbon materials and carbon materials, the existing technology often adopts melt blending or mechanical mixing technology. In the melt blending process, large-sized graphite is easily broken under strong shear force, which leads to a decrease in the conductivity of the bipolar plate and an increase in the air permeability; in order to achieve a good dispersion effect of carbon materials, multiple melt blending is often required in actual production, which will cause the degradation of organic polymers and reduce the bending strength of the bipolar plate; at the same time, a large amount of polymer will accumulate on the surface of the graphite after melt blending, and will accumulate on the surface of the bipolar plate under the action of pressure during the molding process, thereby increasing the contact resistance of the bipolar plate and reducing the conductivity; mechanical mixing often uses ball milling or three-dimensional mixers for mixing, and ball milling mixing will cause part of the carbon material to adhere to the graphite surface, so that it cannot play the effect of penetrating the conductive network material, and the utilization rate of carbon materials is low; the shear force of the three-dimensional mixer is too small to effectively disperse the carbon material, resulting in a decrease in the bending strength, air tightness and conductivity of the bipolar plate; and the solution mixing technology has large pollution, low efficiency, long process, low economy and environmental protection. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a composite material bipolar plate with high conductivity and high mechanical properties for an all-vanadium liquid flow battery.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a composite material bipolar plate for an all-vanadium liquid flow battery, comprising the following steps:
[0008] (1) mixing graphite and an organic polymer and then ball milling to obtain a main mixture of organic polymer-coated graphite;
[0009] (2) mixing and stirring an organic high molecular polymer, a carbon material, a lubricant, and a coupling agent to obtain a mixed powder; adding the mixed powder to a twin-screw extruder for melt blending to obtain a blend; granulating the blend, crushing it, and sieving it to obtain a masterbatch powder;
[0010] (3) The main mixture is mixed with the masterbatch powder and molded to obtain a composite bipolar plate for an all-vanadium liquid flow battery.
[0011] Preferably, in step (1), the graphite is any one of flake graphite, expanded graphite or artificial graphite, and the size of the graphite is 32-150 mesh; the organic polymer is any one of polyethylene, polypropylene or polyvinylidene fluoride, and the particle size of the organic polymer is 1000-2000 mesh, and the melt index is 0.5-3g / 10min.
[0012] Preferably, in step (1), the mass ratio of the organic high molecular polymer to the graphite is 1:10-20.
[0013] Preferably, in step (2), the organic high molecular polymer is of the same type as the organic high molecular polymer in step (1); the carbon material is at least one of graphite powder, carbon black, carbon nanotubes, Ketjen black, or graphene; the lubricant is any one of polyethylene wax, paraffin wax, polypropylene wax, or stearic acid; and the coupling agent is any one of a silane coupling agent or a titanate coupling agent.
[0014] Preferably, in step (2), the mass ratio of the organic high molecular polymer, the carbon material, the coupling agent and the lubricant is 13-26.6:2-10:0.5-1:0.5-1.
[0015] Preferably, in step (2), the particle size of the masterbatch powder is 200-400 mesh.
[0016] Preferably, in step (3), the mass ratio of the main mixture to the masterbatch powder is 0.4-0.6:0.6-0.4.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0018] The existing melt blending technology will destroy the structure of graphite due to excessive shear force, increase the contact resistance between graphites, and increase the defects in the bipolar plate, thereby causing the bending performance, air tightness, and conductivity of the bipolar plate to decrease. The present invention first mixes graphite with an organic high molecular polymer and then ball mills it to obtain a main mixture of organic high molecular polymer coated graphite. The graphite does not need to be dispersed through melt blending, which protects the structure of the graphite, thereby improving the bending performance, air tightness, and conductivity of the bipolar plate.
[0019] The existing melt blending technology will wrap a very thick layer of organic polymer on the graphite surface, because the organic polymer has high fluidity under melt conditions. The present invention uses the physical effects of extrusion, impact, friction, etc. between the ball-milled particles to coat a small amount of organic polymer on the graphite surface, reducing the thickness of the polymer layer on the graphite surface; and by preparing the masterbatch powder, a large amount of carbon material is doped into the polymer to increase the melt viscosity of the polymer. On the other hand, the particle size of the masterbatch powder is controlled at 200-400 mesh, which inhibits the fluidity of the polymer in the melt state, thereby reducing the contact resistance of the bipolar plate.
[0020] In order to achieve uniform mixing of carbon materials of different dimensions, the existing melt blending technology requires long-term melt blending or multiple melt blending, which will cause thermal degradation of organic polymers, thereby resulting in a decrease in the bending strength of the bipolar plate, as well as higher energy consumption and lower production efficiency. The present invention achieves step-by-step mixing of carbon materials of different sizes through steps (1) and (2), thereby improving the mixing efficiency and shortening the mixing time.
[0021] Existing single mixing technologies such as three-dimensional mixing and ball milling cannot simultaneously achieve uniform dispersion of polymers, carbon materials and graphite, resulting in more defects in the bipolar plate, lower bending strength and lower conductivity of the bipolar plate. The present invention achieves step-by-step mixing of carbon materials of different sizes through steps (1) and (2), thereby achieving uniform dispersion of polymers, carbon materials and graphite, and improving the bending strength and conductivity of the bipolar plate.
[0022] By controlling the ratio of the main mixed material to the masterbatch powder within the range of 1-1.5:1.5-1, the bipolar plate prepared by the present invention has an appropriate ratio of carbon material, polymer and graphite, fewer internal defects of the bipolar plate, less surface polymer accumulation, and higher bending strength of the bipolar plate.
[0023] The present invention adopts a tandem twin-screw extruder to prepare the masterbatch powder. Compared with the common intermeshing co-rotating twin-screw extruder, it has better conveying capacity, can reduce the time of melt blending to prevent polymer degradation, and compared with the non-intermeshing co-rotating twin-screw extruder, it has stronger shear force to help disperse the carbon material in the polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the preparation method of the composite material bipolar plate in the present invention. DETAILED DESCRIPTION
[0025] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. Example 1
[0026] (1) Polyethylene powder (2000 mesh, melt index 3 g / 10 min) and expanded graphite (32 mesh) were weighed in a mass ratio of 1:10, dried, and ball-milled at a speed of 50 r / min for 6 h to obtain a main mixture;
[0027] (2) Carbon material, polyethylene powder (2000 mesh, melt index of 3 g / 10 min), polyethylene wax, and silane coupling agent were weighed in a mass ratio of 10:13:1:1. The carbon material was graphite powder and carbon nanotubes in a mass ratio of 4:1. After drying, the mixture was mixed using a three-dimensional mixer to obtain a mixed powder.
[0028] (3) blending the mixed powder obtained in step (2) through a series twin-screw extruder at 170° C. and a rotation speed of 40 r / min to obtain a blend, and granulating, crushing, and sieving to obtain a 200-mesh masterbatch powder;
[0029] (4) The main mixture and the masterbatch powder were mixed in a three-dimensional mixer at a mass ratio of 1.5:1 and then molded at 170°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Example 2
[0030] (1) Polypropylene powder (1700 mesh, melt index 2 g / 10 min) and flake graphite (50 mesh) were weighed in a mass ratio of 1:12.5, dried, and ball-milled at a speed of 100 r / min for 5 h to obtain a main mixture;
[0031] (2) Carbon material, polypropylene powder (1700 mesh, melt index of 2 g / 10 min), polypropylene wax, and titanate coupling agent were weighed in a mass ratio of 8:16.9:0.8:0.8, respectively; the carbon material was graphite powder, carbon nanotubes, and Ketjen black in a mass ratio of 3:1:1; the mixture was dried and mixed using a three-dimensional mixer to obtain a mixed powder;
[0032] (3) The mixed powder obtained in step (2) is blended through a series twin-screw extruder at 200° C. and a rotation speed of 50 r / min to obtain a blend, and then granulated, crushed, and sieved to obtain a 250-mesh masterbatch powder;
[0033] (4) The main mixture and the masterbatch powder were mixed in a three-dimensional mixer at a mass ratio of 1.25:1 and then molded at 200°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Example 3
[0034] (1) Polyethylene powder (1500 mesh, melt index of 1.5 g / 10 min) and artificial graphite (80 mesh) were weighed in a mass ratio of 1:15, dried, and ball-milled at a speed of 150 r / min for 4 h to obtain a main mixture;
[0035] (2) Carbon material, polyethylene powder (1500 mesh, melt index of 1.5 g / 10 min), polyethylene wax, and silane coupling agent were weighed in a mass ratio of 6:20.4:0.7:0.7, respectively. The carbon material was graphite powder and Ketjen black in a mass ratio of 4:1. The mixture was dried and mixed with a three-dimensional mixer to obtain a mixed powder.
[0036] (3) The mixed powder obtained in step (2) is blended at 180° C. and a rotation speed of 40 r / min through a series twin-screw extruder to obtain a blend, and after granulation, crushing and sieving, a 300-mesh masterbatch powder is obtained;
[0037] (4) The main mixture and the masterbatch powder were mixed in a three-dimensional mixer at a mass ratio of 1:1 and then molded at 170°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Example 4
[0038] (1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min) and flake graphite (100 mesh) in a mass ratio of 1:17.5, dry them, and then ball mill them at a speed of 175 r / min for 4.5 h to obtain a main mixture;
[0039] (2) Weighing carbon material, polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min), stearic acid, and titanate coupling agent in a mass ratio of 4:23.6:0.6:0.6, respectively; the carbon material is graphite powder, carbon nanotubes and graphene in a mass ratio of 3:1:1; drying, and mixing with a three-dimensional mixer to obtain a mixed powder;
[0040] (3) blending the mixed powder obtained in step (2) through a series twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and granulating, crushing, and sieving to obtain a 350-mesh masterbatch powder;
[0041] (4) The main mixture and the masterbatch powder were mixed evenly in a mass ratio of 1:1.25 and molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Example 5
[0042] (1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index 0.5 g / 10 min) and expanded graphite (150 mesh) in a mass ratio of 1:20, dry them, and then ball mill them at a speed of 200 r / min for 5.5 h to obtain a main mixture;
[0043] (2) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 0.5 g / 10 min), carbon material, paraffin wax, and silane coupling agent in a mass ratio of 2:26.6:0.5:0.5, respectively, wherein the carbon material is graphite powder, dry the mixture, and mix the mixture using a three-dimensional mixer to obtain a mixed powder;
[0044] (3) blending the mixed powder obtained in step (2) through a series twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and granulating, crushing, and sieving to obtain a 400-mesh masterbatch powder;
[0045] (4) The main mixture and the masterbatch powder were mixed in a three-dimensional mixer at a mass ratio of 1:1.5 and then molded at 180°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Comparative Example 1
[0046] Graphite, carbon material, organic high polymer, coupling agent and lubricant of the same mass and type as in Example 4 were weighed and added into a three-dimensional mixer for stirring and mixing. The obtained mixed powder was molded at 190° C. and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Comparative Example 2
[0047] Graphite, carbon material, organic high polymer, coupling agent and lubricant of the same mass and type as in Example 4 are weighed, added into a tandem twin-screw extruder and mixed at 190°C and 60 r / min to obtain a premixture, which is granulated and then added into the tandem twin-screw extruder again and mixed at 190°C and 60 r / min to obtain a mixture, which is granulated and sieved, and molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for an all-vanadium liquid flow battery. Comparative Example 3
[0048] 1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min) and flake graphite (100 mesh) in a mass ratio of 1:17.5, dry them, and then ball mill them at a speed of 175 r / min for 4.5 h to obtain a main mixture;
[0049] (2) Weighing carbon material, polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min), stearic acid, and titanate coupling agent in a mass ratio of 4:23.6:0.6:0.6, respectively; the carbon material is graphite powder, carbon nanotubes and graphene in a mass ratio of 3:1:1; drying, and mixing with a three-dimensional mixer to obtain a mixed powder;
[0050] (3) blending the mixed powder obtained in step (2) through a series twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and granulating, crushing, and sieving to obtain a 300-mesh masterbatch powder;
[0051] (4) The main mixture and the masterbatch powder were mixed evenly in a mass ratio of 1:2 and molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Comparative Example 4
[0052] 1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min) and flake graphite (100 mesh) in a mass ratio of 1:17.5, dry them, and then ball mill them at a speed of 175 r / min for 4.5 h to obtain a main mixture;
[0053] (2) Weighing carbon material, polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min), stearic acid, and titanate coupling agent in a mass ratio of 4:23.6:0.6:0.6, respectively; the carbon material is graphite powder, carbon nanotubes and graphene in a mass ratio of 3:1:1; drying, and mixing with a three-dimensional mixer to obtain a mixed powder;
[0054] (3) The mixed powder obtained in step (2) is blended through a counter-rotating conical twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and after granulation, crushing and sieving, a 300-mesh masterbatch powder is obtained;
[0055] (4) The main mixture and the masterbatch powder were mixed evenly in a mass ratio of 2:1 and then molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Comparative Example 5
[0056] 1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min) and flake graphite (100 mesh) in a mass ratio of 1:17.5, dry them, and then ball mill them at a speed of 175 r / min for 4.5 h to obtain a main mixture;
[0057] (2) Weighing carbon material, polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min), stearic acid, and titanate coupling agent in a mass ratio of 4:23.6:0.6:0.6, respectively; the carbon material is graphite powder, carbon nanotubes and graphene in a mass ratio of 3:1:1; drying, and mixing with a three-dimensional mixer to obtain a mixed powder;
[0058] (3) The mixed powder obtained in step (2) is blended through a counter-rotating conical twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and after granulation, crushing and sieving, a 300-mesh masterbatch powder is obtained;
[0059] (4) The main mixture and the masterbatch powder were uniformly mixed in a mass ratio of 1:1.25 and molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery. Comparative Example 6
[0060] 1) Weigh polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min) and flake graphite (100 mesh) in a mass ratio of 1:17.5, dry them, and then ball mill them at a speed of 175 r / min for 4.5 h to obtain a main mixture;
[0061] (2) Weighing carbon material, polyvinylidene fluoride powder (1000 mesh, melt index of 1 g / 10 min), stearic acid, and titanate coupling agent in a mass ratio of 4:23.6:0.6:0.6, respectively; the carbon material is graphite powder, carbon nanotubes and graphene in a mass ratio of 3:1:1; drying, and mixing with a three-dimensional mixer to obtain a mixed powder;
[0062] (3) blending the mixed powder obtained in step (2) through a series twin-screw extruder at 190° C. and a rotation speed of 60 r / min to obtain a blend, and granulating, crushing, and sieving to obtain a 600-mesh masterbatch powder;
[0063] (4) The main mixture and the masterbatch powder were mixed evenly in a mass ratio of 1:1.25 and molded at 190°C and 15 MPa for 10 min to obtain a composite material bipolar plate for all-vanadium liquid flow battery.
[0064] The bipolar plates prepared in the examples and comparative examples were tested according to NB / 42007-2013, test method for bipolar plates for all-vanadium liquid flow batteries. The conductivity value was the reciprocal of the volume resistivity in the method. The test results are shown in Table 1.
[0065] .
[0066] It can be seen from the data in the above table that the conductivity of Examples 1-5 increases with the increase of the carbon material content in the bipolar plate, and the contact resistance decreases with the increase of the carbon material content.
[0067] It can be seen from the data in the above table that the contact resistance and conductivity of Example 4 are better than those of Comparative Example 1. This is because the single three-dimensional mixing shear force is too small to simultaneously achieve uniform dispersion of the polymer, carbon material, and graphite, resulting in more defects in the bipolar plate of Comparative Example 1, lower bending strength of the bipolar plate, lower conductivity, and higher permeability.
[0068] It can be seen from the data in the above table that the conductivity, air permeability, bending strength and contact resistance performance of Comparative Example 2 are all worse than those of Example 4. This is because the shear force of the twin-screw extruder on the graphite is relatively large during the melt blending process, which destroys the original structure of the graphite and is not conducive to the construction of the conductive network in the bipolar plate, so the conductivity of the bipolar plate decreases. Moreover, due to the destruction of the graphite structure, the channels formed by the pores in the bipolar plate become more and more, and the channels become smoother, so the air permeability of the bipolar plate is improved. And long-term melt blending will cause thermal degradation of organic polymers, thereby causing the bending strength of the bipolar plate to decrease. Comparative Example 4 uses physical effects such as extrusion, impact, and friction between ball-milled particles to coat a small amount of organic polymer on the surface of graphite, reducing the thickness of the polymer layer on the graphite surface; and by preparing a masterbatch powder, a large amount of carbon material is doped in the polymer to increase the melt viscosity of the polymer, inhibit the fluidity of the polymer in the melt state, thereby reducing the contact resistance. Comparative Example 2 uses melt blending technology, which will wrap a thick organic polymer layer on the graphite surface. This is because the organic polymer has high fluidity under melt conditions. Therefore, the conductive performance and contact resistance of Example 2 are poor.
[0069] It can be seen from the data in the above table that the bending performance, conductivity, permeability and contact resistance performance of Comparative Example 3 are worse than those of Example 4. This is because the proportion of masterbatch powder is too high, resulting in an excessively high content of carbon material in the bipolar plate, agglomeration occurs, and the bending performance decreases and the contact resistance increases; on the other hand, due to the reduction in graphite content, the contact resistance between the conductive carbon materials in the system increases, resulting in a decrease in the conductivity of the bipolar plate. At the same time, the conductive path of the bipolar plate is imperfect and there are more defects in the plate, which increases the permeability of the bipolar plate and decreases the conductivity.
[0070] It can be seen from the data in the above table that the conductivity and permeability of Comparative Example 4 are worse than those of Example 4. This is because the proportion of masterbatch powder is low, resulting in a low content of carbon material in the bipolar plate, which cannot fill the gap between graphite and polymer, so the conductivity and permeability of the bipolar plate are poor.
[0071] It can be seen from the data in the above table that the conductivity, air permeability and bending strength of Comparative Example 5 are worse than those of Example 4. This is because the counter-rotating conical twin-screw extruder has a strong ability to convey materials but a low shear force, which cannot achieve a good dispersion of the carbon material, resulting in agglomeration of the carbon material and more internal defects in the bipolar plate, so the performance of the bipolar plate is poor.
[0072] It can be seen from the data in the above table that the conductivity and contact resistance of Comparative Example 6 are worse than those of Example 4. This is because the particle size of the masterbatch powder is too small, which leads to a fast melting rate and strong fluidity of the masterbatch powder during the molding process, and it gathers on the surface of the bipolar plate during the spreading process, thereby increasing the contact resistance of the bipolar plate and decreasing the conductivity.
Claims
1. A method for preparing a composite material bipolar plate for an all-vanadium liquid flow battery, characterized in that: The steps include: (1) mixing graphite and an organic polymer and then ball milling to obtain a main mixture of organic polymer-coated graphite; (2) Mixing and stirring an organic high molecular polymer, a carbon material, a lubricant, and a coupling agent to obtain a mixed powder; adding the mixed powder to a tandem twin-screw extruder for melt blending to obtain a blend; granulating the blend, crushing, and sieving to obtain a masterbatch powder; the particle size of the masterbatch powder is 200-400 mesh; (3) The main mixture is mixed with the master batch powder, and then molded to obtain a composite material bipolar plate for an all-vanadium liquid flow battery; the mass ratio of the main mixture to the master batch powder is 1-1.5:1.5-1.
2. The preparation method according to claim 1, characterized in that: In the step (1), the graphite is any one of flake graphite, expanded graphite or artificial graphite, and the size of the graphite is 32-150 mesh; the organic high molecular polymer is any one of polyethylene, polypropylene or polyvinylidene fluoride, and the particle size of the organic high molecular polymer is 1000-2000 mesh, and the melt index is 0.5-3g / 10min.
3. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the organic high molecular polymer to the graphite is 1:10-20.
4. The preparation method according to claim 1, characterized in that: In the step (2), the organic high molecular polymer is of the same type as the organic high molecular polymer in the step (1); the carbon material is at least one of graphite powder, carbon black, carbon nanotubes, Ketjen black, or graphene; the lubricant is any one of polyethylene wax, paraffin wax, polypropylene wax, or stearic acid; and the coupling agent is any one of a silane coupling agent or a titanate coupling agent.
5. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the organic high molecular polymer, the carbon material, the coupling agent and the lubricant is 13-26.6:2-10:0.5-1:0.5-1.
Citation Information
Patent Citations
Method for preparing calcium carbonate-YSZ composite solid electrolyte by ultrasonic microwave combination method
CN111517783A
Thermoplastic composite bipolar plate for flow battery as well as preparation method and application of thermoplastic composite bipolar plate
CN117133936A